GRAMMATICAL CONSCIOUSNESS ON ENGLISH MEDIO-PASSIVE CONSTRUCTIONS: IS IT ESSENTIAL FOR EFL TEACHERS’ COMPETENCY STANDARD? - Jufrizal Jufrizal (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2014)
Most EFL learners in Indonesia have already known that English grammatically has active and passive con-structions. However, the so called medio-passive constructions in English have not been seriously introduced and understood by many EFL learners; they do not have sufficient knowledge and “grammatical conscious-ness” on the stylistic constructions, then. The lack of understanding and grammatical consciousness may raise academic and psychological problems on English grammar. Such lack of grammatical consciousness may academically affect both learners’ and teachers’ competency standards. Many students cannot use gram-matical and communicative English appropriately in academic and practical uses. This paper briefly dis-cusses the academic need for grammatical consciousness on the medio-passive constructions as part of learn-ers’ and teachers’ competency standards in EFL, particularly in multilingual speakers like in Indonesia. Key words/phrases: medio-passive, grammatical consciousness, EFL, competency standards